2017
DOI: 10.1001/jamapsychiatry.2017.2228
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter With Core Cognitive Deficits in Patients With Schizophrenia

Abstract: Study findings suggest that (1) processing speed contributes to the association between white matter microstructure and working memory in schizophrenia and (2) white matter impairment in schizophrenia is regional tract-specific, particularly in tracts normally supporting processing speed performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 49 publications
14
92
1
1
Order By: Relevance
“…The details of DTI data preprocessing were described in Supplementary Material and our previous studies(35, 43). Based on a tract-based spatial statistics method(44), fractional anisotropy(FA) images were obtained, spatially normalized to the JHU atlas(45) which separated white matter into different tracts.…”
Section: Methodsmentioning
confidence: 99%
“…The details of DTI data preprocessing were described in Supplementary Material and our previous studies(35, 43). Based on a tract-based spatial statistics method(44), fractional anisotropy(FA) images were obtained, spatially normalized to the JHU atlas(45) which separated white matter into different tracts.…”
Section: Methodsmentioning
confidence: 99%
“…Lower integrity of cerebral white matter (WM), quantified as reduced fractional anisotropy (FA) of water diffusion measured from diffusion tensor imaging (DTI), is a consistent finding in schizophrenia (Alba-Ferrara & de Erausquin 2013;Ellison-Wright & Bullmore 2009;Friedman et al, 2008;Glahn et al, 2013;Kelly et al, 2017;Kochunov & Hong 2014;Kubicki et al, 2007;Nazeri et al, 2012;Perez-Iglesias et al, 2011;Phillips, Rogers, Barrett, Glahn, & Kochunov, 2012;Wright et al, 2015). FA deficits are hypothesized to be prominent in the associative WM fibers and responsible for neuropsychological deficits association *Peter Kochunov, Erin W. Dickie, and Joseph D. Viviano contributed equally to this study.…”
Section: Introductionmentioning
confidence: 96%
“…Lower integrity of cerebral white matter (WM), quantified as reduced fractional anisotropy (FA) of water diffusion measured from diffusion tensor imaging (DTI), is a consistent finding in schizophrenia (Alba‐Ferrara & de Erausquin ; Ellison‐Wright & Bullmore ; Friedman et al, ; Glahn et al, ; Kelly et al, ; Kochunov & Hong ; Kubicki et al, ; Nazeri et al, ; Perez‐Iglesias et al, ; Phillips, Rogers, Barrett, Glahn, & Kochunov, ; Wright et al, ). FA deficits are hypothesized to be prominent in the associative WM fibers and responsible for neuropsychological deficits association with this disorder (Ellison‐Wright & Bullmore ; Friedman et al, ; Kochunov et al, ; Kubicki et al, ; Nazeri et al, ; Perez‐Iglesias et al, ). A challenge for evaluating regional WM deficits is the need for statistically powerful and representative samples that can be difficult to collect at a single site (Ioannidis ; Jahanshad et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of those studies has found that deficits in working memory and reduced speed in information processing, two of the fundamental cognitive deficits in schizophrenia, are associated with impaired whole-brain white matter microstructure [51]. In deficit syndrome schizophrenia, characterized by prominent negative symptoms and poor functional outcome [52], impairments in specific white matter tracts have been found, particularly in the uncinate fasciculus, inferior longitudinal fasciculus, and arcuate fasciculus [53].…”
Section: Structural Connectivitymentioning
confidence: 99%